2004
DOI: 10.1074/jbc.m403959200
|View full text |Cite
|
Sign up to set email alerts
|

Drug Uptake and Modulation of Drug Resistance in Leishmania by an Aquaglyceroporin

Abstract: Leishmaniasis is a protozoan parasitic disease that affects 12 million people worldwide. The first line choice for the treatment of this disease is antimonial drugs. In the endemic regions, resistance to this class of drugs is a major impediment to treatment. Microbes often become resistant to drugs by mutation or down-regulation of uptake systems, but the uptake system for the antimonial drugs in Leishmania is unknown. In other organisms, aquaglyceroporins have been shown to facilitate uptake of trivalent met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
231
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(245 citation statements)
references
References 37 publications
7
231
0
7
Order By: Relevance
“…The LmxMIT::GFP fusion protein was generated by cloning the LmxMIT ORF into the BamHI and EcoRV sites of pXG-ЈGFP ϩ (26). The LmjAQP1 ORF was amplified using previously described primers (27) with KpnI and EcoRV restriction sites and cloned into the pX72-Hyg vector described above. All primer sequences are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…The LmxMIT::GFP fusion protein was generated by cloning the LmxMIT ORF into the BamHI and EcoRV sites of pXG-ЈGFP ϩ (26). The LmjAQP1 ORF was amplified using previously described primers (27) with KpnI and EcoRV restriction sites and cloned into the pX72-Hyg vector described above. All primer sequences are available upon request.…”
Section: Methodsmentioning
confidence: 99%
“…Trivalent form of the antimonial drug (SbIII) is the prodrug that is formed by conversion of pentavalent antimony (SbV) by a putative metalloid reductase present in the macrophages [28]. Antimonial resistance in both laboratory mutants and clinical isolates has been associated with (a) decreased uptake of the drug through aquaglyceroporin (AQP1) that codes for the protein responsible for SbIII transport Nepjol.info/index.php/njb [11,12,20,29] (b) Over expression of ODC and γ-GCS enzymes of the trypanothione biosynthetic pathway [2,25] and (c) increased expression of the ABC transporter MRPA, which sequesters SbIII-thiol conjugate [16,23]. We had earlier reported decreased uptake of antimony in all nine SAG-R isolates used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of drug activation is reported to lead to resistance [10]. The route of entry of SbV into Leishmania cells is still unknown but SbIII has been reported to be transported in Leishmania through aquaglyceroporin (AQP1) [11,12]. Recent evidence has suggested that part of the mode of ©NJB, Biotechnology Society of Nepal 2 Nepjol.info/index.php/njb action of SbV could be in depleting the cells of its reduced thiols [13].…”
Section: Introductionmentioning
confidence: 99%
“…An increased protein turnover rate of KMP-11 was observed in the resistant parasites. It was suggested by the authors that the decreased expression/accelerated turnover rate of KMP-11 could lead to an increased export of Sb(III) due to an alteration of putative efflux systems 57 or transporters, such as the aquaglyceroporin 58 .…”
Section: Vergnes and Colleagues Used 2de Resolved Proteomes Of Antimomentioning
confidence: 99%